Alexithymia and Somatization in Chronic Pain Patients: A Sequential Mediation Model - Lanzara, Roberta; Conti, Chiara; Camelio, Martina; Cannizzaro, Paolo; Lalli, Vittorio; Bellomo, Rosa Grazia; Saggini, Raoul; Porcelli, Piero (Frontiers in Psychology, 2020)
Objective: To investigate whether chronic pain (CP) patients with somatization had higher alexithymic traits than those without somatization and to explore the different relationship between psychological features, pain, health-related quality of life (HRQL), and somatization. Method: A consecutive sample of 134 CP treatment-seeking outpatients were evaluated for alexithymia (TAS-20), somatization (PHQ-15), distress (HADS), HRQL (SF-12), and pain (BPI). Results: Patients with somatization (37.04%) reported significantly higher TAS‐20 total scores (p<.001) and difficulty in identifying feelings (DIF) (p<.001) than those without somatization. The somatizer group had also a significantly higher disease duration, severity and interference of pain, distress, and lower HRQL than the non-somatizer group. Hierarchical regression analysis showed that although distress, pain interference and the mental HRQL component are closely related to somatization (R2=0.55), DIF was the strongest predictor of severity of somatization (β=0.31). A sequential indirect effect from DIF to somatization via distress symptoms and pain interference turned out to be significant [95% CI (0.01, 0.09)]. Support was also found for sequential mediation paths from DIF to somatization via distress and mental HRQL [95% CI (0.01, 0.11)]. Conclusions: Our study suggests that alexithymia, particularly DIF, may be considered a major psychological factor for somatization risk in CP patients. Longitudinal studies are needed for investigating the role of alexithymia in clinical outcomes.